2009
DOI: 10.1002/bjs.6687
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and potential risk factors for gallstone disease in a general population sample

Abstract: The incidence of gallstones in this population was 1.39 per 100 person-years. Gallstone development was related to length of follow-up and LDL-cholesterol levels, and inversely related to alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 41 publications
8
50
3
Order By: Relevance
“…As for gender, our results are consistent with the generally accepted view that gallstone prevalence is higher in women than in men [32,33]. Quite a few studies revealed a positive correlation between a high serum LDL level and cholesterol gallstone development [34,35]; the results of our study displayed a relationship between a high serum LDL level and GD prevalence, though we failed to get the information of the gallstone type. However, some reports have showed that there is no relation between serum LDL level and the presence of gallstones [36,37].…”
Section: Discussionsupporting
confidence: 82%
“…As for gender, our results are consistent with the generally accepted view that gallstone prevalence is higher in women than in men [32,33]. Quite a few studies revealed a positive correlation between a high serum LDL level and cholesterol gallstone development [34,35]; the results of our study displayed a relationship between a high serum LDL level and GD prevalence, though we failed to get the information of the gallstone type. However, some reports have showed that there is no relation between serum LDL level and the presence of gallstones [36,37].…”
Section: Discussionsupporting
confidence: 82%
“…The natural course of GSD is typically benign; however, its complications contribute substantially to healthcare costs and may even be life threatening [15]. A crucial benefit of early detection for GSD is that ultrasonography can detect asymptomatic cases, enabling appropriate treatment and prevention of serious influences such as acute gallstone pancreatitis or gallbladder cancer [16,17].…”
Section: Clinical Implications Of Gallstone Disease Screeningmentioning
confidence: 99%
“…Among them, 1-3% become symptomatic and seek medical treatment. The gold standard treatment of cholelithiasis is gallbladder surgical removal, which is one of the most commonly performed surgical procedures worldwide [3,4,5]. Open surgical removal of the gallbladder was performed as a gold standard procedure for treatment in the period before 1988.…”
Section: Introductionmentioning
confidence: 99%